Malvadin Prevents Kidney from Renal Ischemia-Induced Oxidative Damage in Rats. Running Title: Malvidin and Acute Renal Failure - Emadi, Sarvenaz; Sadeghi, Iman; Khastar, Hossein (Jordan Journal of Pharmaceutical Sciences, 2020)
Background: Oxidative stress is one of the suggested causes of renal ischemia reperfusion (IR) injury. Malvidin is an important anthocyanin which exhibits significant antioxidant properties. Here, we aimed to study the effect of Malvidin on oxidative stress status in vivo. Materials and Methods: 30 Male Wistar rats were randomly assigned to three groups: (1) Sham operated, (2) renal IR (45 min ischemia followed by 24 h of reperfusion), (3) renal IR + Malvidin (100 mg/kg, P.O, 21 days). In IR group, rats were anesthetized and renal arteries occluded for 45 min followed by 24 h reperfusion. Sham-operated Rats underwent a surgical procedure identical to those of IR rats except that clamps were not applied. Then, renal functional indices (fractional excretion of sodium, plasma (blood urea nitrogen) BUN, creatinine (Cr), urine flow rate, creatinine clearance) and oxidative stress indices such as catalase (CAT), superoxide dismutase (SOD) and malondialdehyde (MDA) were evaluated in blood and kidney tissue.Results: Malvidin caused a fall in fractional excretion of Na, plasma BUN, Cr and rise in urine flow rate, Cr clearance in malvidin group compared with IR group. In addition malvidin administration resulted in an increase in CAT and SOD and decrease in MDA in contrast to IR group.Conclusion: malvidin consumption has protective effect against renal IR induced acute kidney injury, partly by inhibiting oxidative stress in renal tissues.